2009
DOI: 10.1515/ijnsns.2009.10.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Porous Materials with Thin Interlayers for Optimal Thermal Insulation

Abstract: The combined radiative and conductive heat transfer through highly porous materials is a typical nonlinear problem in engineering thermal insulations. The complexity of the integral radiative and conductive heat transfer equations especially the nonlinearity of the heat radiation item makes it extremely difficult to obtain exact solution. A theoretical model was developed based on the combined radiative and conductive heat transfer through the highly porous materials with thin interlayers and numerically solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Fibrous porous media have attracted considerable attention in natural and technological processes including thermal insulation, fuel cells, biological transport phenomena, filtration and separation, and production of textiles and paper [1][2][3][4][5][6][7][8][9]. One of the most important properties for fibrous porous media is permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrous porous media have attracted considerable attention in natural and technological processes including thermal insulation, fuel cells, biological transport phenomena, filtration and separation, and production of textiles and paper [1][2][3][4][5][6][7][8][9]. One of the most important properties for fibrous porous media is permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the polymer matrix is fixed due to the diffusion of sc-fluid molecules out of the matrix and the related increase of T g *. Finally, a nanoporous polymer is obtained which can be used in heat insulation [32,33], gas storage [34], separation [35], and catalysis [36]. Using the porous polymer as a template itself, Qawasmi et al [37] have mineralized porous polystyrene (PS), previously prepared by the NF-CID method, at mild conditions via chemical bath deposition (CBD) with a ZnO precursor solution.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [5] measured TCR between grapheme and silicon dioxide by using a differential method. Wu et al [6] found that the thermal resistances of porous materials could be effectively improved by adding appropriate number of interlayer of appropriate thickness. Although the surface morphology is known as a key factor of TCR [7], the roughness has been used only as a parameter in the previous studies [8] and little work has been done on the influence of surface morphology.…”
Section: Introductionmentioning
confidence: 99%